PERUBAHAN SOSIAL DAN KAITANNYA DENGAN PEMBAGIAN HARTA WARISAN DALAM PERSPEKTIF HUKUM ISLAM - Zulham Wahyunadi; Raihanah HJ Azahari (Islam Futura, 2015)
This article generally discusses the social change and its relationship to the practice of Islamic inheritance. This study aims to investigate the impact of the social change in altering the inheritance law. Data for this study were gathered through various Islamic literatures, books, articles, seminar papers and other related materials. The findings of this study revealed that the social change has influence on the altering of the Islamic inheritance law within the community. However, the change was limited only for the law that was resulted from maslahah al-mursalah, as wasīyyat al- wajībah problems that have been legislated laws in Muslim countries, not the qat‘i laws as it was originally coming from the divine source. As this study has several limitations, it was recommended that future studies need to examine this matter more comprehensively due to some deficiencies in its application such as the use of fiqh and ushul methods.